Analysis of methylation‐driven genes for predicting the prognosis of patients with head and neck squamous cell carcinoma. Issue 12 (1st July 2019) - Pan, Yihua; Song, Yidan; Cheng, Lanxin; Xu, Hongdan; Liu, Jun
Abstract: To help provide evidence for prognosis prediction and personalized targeted therapy for patients with head and neck squamous cell carcinoma (HNSCC), we investigated prognosis‐specific methylation‐driven genes in HNSCC. Survival time data, RNA sequencing data, and methylation data for HNSCC patients were downloaded from The Cancer Genome Atlas. The MethylMix R package based on the β mixture model was utilized to screen genes with different methylation statuses in tumor tissues and adjacent normal tissues, and a total of 182 HNSCC‐related methylation‐driven genes were then identified. A survival prediction scoring model based on multivariate Cox analysis was developed to screen the genes related to the prognosis of HNSCC, and a linear risk model of the methylation status of six genes ( INA, LINC01354, TSPYL4, MAGEB2, EPHX3, and ZNF134 ) was constructed. The prognostic values of the six genes were further independently explored by survival analysis combined with methylation and gene expression analyses. The 5‐year survival rate in the high‐risk group of patients in the test set was 30.4% (95% CI: 22.7%‐40.8%) and that in the low‐risk group of patients was 65.5% (95% CI: 56.1%‐76.5%). The area under the receiver operating characteristic curve for the model was 0.723, which further verified the specificity and sensitivity of the model. In addition, subsequent combined survival analysis revealed that all six genes could be used as independent prognostic markers and thus might be potential drug targets. The innovative method provides new insight into the molecular mechanism and prognosis of HNSCC. Abstract : In this study, we investigated prognosis‐specific methylation‐driven genes in head and neck squamous cell carcinoma (HNSCC) to help provide evidence for prognosis prediction and personalized targeted therapy for patients with HNSCC. We used an innovative method which provides new insight into the molecular mechanism and prognosis of HNSCC.